Growth, biomass, and chlorophyll-a and carotenoid content of Nannochloropsis sp. strain BJ17 under different light intensities - Muhammad Fakhri; Nasrullah Bai Arifin; Anik Martina Hariati; Ating Yuniarti (Jurnal Akuakultur Indonesia)
ABSTRACT